2015
DOI: 10.1063/1.4927566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stacking disorder on thermal conductivity of cubic ice

Abstract: This is the published version of a paper published in J. Chem. Phys. Citation for the original published paper (version of record):Johari,G.P., Andersson, O. (2015) Effects of stacking disorder on thermal conductivity of cubic ice J. Chem. Phys., 143, 054505 (2015).Access to the published version may require subscription. N.B. When citing this work, cite the original published paper. Cubic ice is said to have stacking disorder when the H 2 O sequences in its structure (space group Fd3m) are interlaced with hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Increase in the impurity concentration changes the viscosity and the intermolecular hydrogen-bond equilibrium of water, extends the supercooling range by preventing crystallization, and changes the crystal phases formed on crystallization of the supercooled state, which may be cubic ice, hexagonal ice, their mixtures, or ice crystals with stacking faults. (A review of the freezing to such crystals was given recently it was found that when ∼100 mL of water at 298 K contained in a flask was “evacuated” by continuous pumping for several hours, it froze from the surface downward, and the hexagonal ice thus formed had enough impurities to decrease its dielectric relaxation or the orientation fluctuation time by several orders of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the impurity concentration changes the viscosity and the intermolecular hydrogen-bond equilibrium of water, extends the supercooling range by preventing crystallization, and changes the crystal phases formed on crystallization of the supercooled state, which may be cubic ice, hexagonal ice, their mixtures, or ice crystals with stacking faults. (A review of the freezing to such crystals was given recently it was found that when ∼100 mL of water at 298 K contained in a flask was “evacuated” by continuous pumping for several hours, it froze from the surface downward, and the hexagonal ice thus formed had enough impurities to decrease its dielectric relaxation or the orientation fluctuation time by several orders of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that the formation of cubic structures, rather than hexagonal structures, in the pores can be attributed to the restrictions on the size of the crystallite. However, according to recently published studies [4,10,[28][29][30][31], the cubic form that has been observed is not exactly cubic. This form of ice, so-called cubic phase, shows stacking faults instead of an ordered arrangement of two-dimensional layers [28].…”
Section: Introductionmentioning
confidence: 97%
“…In general, it is assumed that under ambient conditions, ice exists in two crystalline forms: stable hexagonal ice (ice I h ) and metastable cubic ice (ice I c ). Usually, water freezes to hexagonal ice which crystallizes in the space group P63/mmc, but under certain conditions, mostly in laboratory, it can freeze to create cubic ice in the space group Fd3m [4]. Both hexagonal and cubic ice consist of layers composed of six-membered rings of hydrogen-bonded water molecules; however, they differ in the arrangement of second-neighbours layer [5].…”
Section: Introductionmentioning
confidence: 99%
“…These claims are being debated since also polycrystals of hexagonal ice 4,5 or trigonal crystals may be of relevance in this context. 6 The higher vapor pressure and the lower thermal conductivity 7 of ice I c as compared to ice I h might be of importance in cloud freezing and persistent in-cloud supersaturations in cold cirrus. 8 Ultimately, larger crystals of ice I h might form via ice I c , thereby more efficiently dehydrating air.…”
Section: Introductionmentioning
confidence: 99%